Pengaruh atribut tata kelola dan karakteristik perusahaan terhadap kebijakan dividen pada perusahaan di BEI - Serly Serly; Mery Susanti (Jurnal Ekonomi Modernisasi, 2021)
The dividend was a kind of return from portfolio investment. Firms in making dividend payment decisions are influenced by several motives. The main topic of the research was to determine the impact of corporate governance and firm characteristics on the decision of dividend policy. In here, corporate governance was focused on board characteristics consisting of board size, independent director, board meeting frequency, woman director, and audit committee size. While the firm characteristics were measured by size, profitability (ROA), and leverage. The research used companies data collected from Indonesia Stock Exchange. Companies data must available from the period 2015-2019 and resulted in 2.175 sample data. The research used the panel regression method. The result of the research proved that board size and profitability (ROA) significantly positively influenced the dividend policy. Board meeting frequency showed a positive effect on dividend per share, but no effect on dividend per asset. Otherwise, women directors and leverage reflected a significant negative effect with dividend per assets, but an insignificant effect on dividend per share. On the other hand, firm size, independent director, and audit committee size did not have any significant impact on dividend policy decisions.